Cobertura, según la necesidad de tratamiento odontológico en los pacientes atendidos en la Clínica Odontológica, de la Universidad Nacional de Loja, durante el año 2014-2015. - Eras Palta, Geovanna Paola (2016)
The present study is descriptive, quantitative and retrospective, for which was taken as a sample 400 clinical histories of patients during the period 2014- 2015; according to gender and age group, with the aim of determining the need for treatment that presented the dental bodies and its adjacent tissues, as well as the percentage of coverage of each treatment, this took into account the records of clinical implementation of each treatment finished, applied the index of need of individual treatment based on the experience generated by the DMFT indices of Klein and Palmer. Then conducted a data dump and through the implementation of statistics formulas were obtained the results of both the need for treatment as the percentage of coverage of the same. It took into account 3 criteria: treatments carried out by dental bodies; by upper and lower dental arches and treatments carried out by patient. The results obtained show that the CPOD index according to age groups (adolescents, young adults, and older adults) media presented a CPOD index with very high severity; being the group of older adults have the greatest severity presented with an index of 21.55. With regard to the coverage of the treatments according to the need of each patient in adolescents is needed fillings between one and more surfaces by obtaining a coverage of 19.60%, treatments pulpar and extractions of which has made the coverage of 100% and 95,65% respectively. In young adults is needed crowns continue the 33,74% coverage, treatments pulpar and extractions of which was the coverage of 93,68% and 91,48% respectively, removable prosthetics between upper and lower arch, continue the coverage of 9.58% and periodontal treatments which were held the 50,34% coverage. In adults media is required crowns continue 44.26% coverage, treatments pulpar and extractions of which the coverage was of 92.15 % and 90,90 % respectively, total prosthesis between upper and lower arch, carried the 42.85% coverage and periodontal treatments being the coverage of 45,58%. In older adults pulpar treatments are needed, extractions and total prosthesis which took place the coverage of 100% respectively, removable prosthetics between upper and lower arch, continue the coverage of 23.07%, finally periodontal treatments which the coverage was of 42.85%. Between Gender Male and female. Key words: Index, need for treatment, Coverage